Study on purchase intention of young generation towards private brand products / Nur Maizatul Syuhada Hashim - Hashim, Nur Maizatul Syuhada (Faculty of Business and Management, 2015)
The primary attempt in this study was to explore the purchase intention of Malaysian towards private brand products. This study explore the relationship between three factors that could motivate and intent Malaysian to buy private brand products are price, perceived quality and social influences. Data collected analysed using Statistical Package for the Social Science (SPSS) for Windows. This study was conducted at Shah Alam which will specifically focus people that shopping at Tesco Seksyen 13. In this study, 100 sets of questionnaires have been distributed. All the respondents will be responding from the questionnaire that will provide to get the result on the purchase intention of Malaysian towards private brand products. All the three major of the independent variables will be explained in the literature review and research framework.